2022
DOI: 10.3390/ani12182368
|View full text |Cite
|
Sign up to set email alerts
|

chi-miR-99b-3p Regulates the Proliferation of Goat Skeletal Muscle Satellite Cells In Vitro by Targeting Caspase-3 and NCOR1

Abstract: We previously found that chi-miR-99b-3p was highly expressed in the skeletal muscle of 7-month-old (rapid growth period) goats and speculated that it may be associated with muscle development. To further investigate the role of chi-miR-99b-3p in goats, we found that chi-miR-99b-3p acted as a myogenic miRNA in the regulation of skeletal muscle development. Dual-luciferase reporter assays, qRT-PCR, and Western blot results confirmed that Caspase-3 and nuclear receptor corepressor 1 were direct targets for chi-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recent research has demonstrated that whereas MYOD, MRF4, MHC, and other genes primarily govern muscle cells fusion, MSTN, Myf5, and IGF-1 are primarily involved in the proliferation of muscle cell 27,28,29,30,31 . The number of muscle cells did not change considerably after transfection of pcDNA3.1 (+)-004686 into chicken primary myoblasts, while the expression of IGF-1, a marker gene for muscle cell proliferation, increased dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that whereas MYOD, MRF4, MHC, and other genes primarily govern muscle cells fusion, MSTN, Myf5, and IGF-1 are primarily involved in the proliferation of muscle cell 27,28,29,30,31 . The number of muscle cells did not change considerably after transfection of pcDNA3.1 (+)-004686 into chicken primary myoblasts, while the expression of IGF-1, a marker gene for muscle cell proliferation, increased dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…ovary [ 45 ], liver [ 46 ], pituitary [ 47 ], lung [ 48 ]) and types of cells (e.g. skeletal muscle satellite cells [ 49 ], skin fibroblast cells [ 50 ], Leydig cells [ 51 ], blood leukocytes and milk somatic cells [ 52 ], intramuscular preadipocytes [ 53 ], endometrial epithelium cells [ 54 ]) in physiological and pathological processes in goats, including in response to infectious diseases. For example, the expression of 316 DEmiRNAs was found in peripheral blood mononuclear cells of goats infected with peste des petits ruminants virus, and most of the predicted targets of these DEmiRNAs were found to be involved in immune escape [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-23a promotes myogenic differentiation of fetal bovine skeletal muscle-derived progenitor cells by targeting the MyoD family inhibitor structural domain-containing (MDFIC) genes [66]. miR-2425-5p targets the 3 -UTR of RAD9 homolog A (RAD9A) and myogenesis (MYOG) to promote proliferation and inhibit differentiation [67] in sheep and goats, including miR-181a, miR-29a, miR-99b-3p, and miR-27a-3p [69][70][71][72] and in rabbits and pigs, including miR-194-5p and miR-22, respectively [80,81]. The specific mechanisms of action of these miRNAs will not be elaborated.…”
Section: Mirnas Are Involved In Skeletal Muscle Development In Satell...mentioning
confidence: 99%